Communication Experiences and Challenges of Kindergarten and Elementary Teachers in Online Learning during the COVID-19 Pandemic - Sri Seti Indriani; Ditha Prasanti (Ikatan Sarjana Komunikasi Indonesia, 2021)
The increasing number of patients recovering from the COVID-19 and the decreasing number of people exposed to the infection seemed to raise the community’s hopes for returning to face-to-face learning. Some schools have slowly implemented face-to-face learning. Teachers sincerely hope to optimize face-to-face learning soon. However, there are still pros and cons over face-to-face learning for fear of schools turning into COVID-19 clusters. The teachers complained about various online learning problems, so they applied for permission to conduct face-to-face learning. The purpose of this research is to understand teachers’ experiences in online learning during the COVID-19 pandemic, including positive and negative experiences as well as obstacles in the online learning during the pandemic. This study uses descriptive qualitative research methods, with data collection technique conducted through documentation studies as well as interviews with five kindergarten and elementary school teachers. The selection of research subjects used purposive sampling. The results of this study revealed that the teachers had extraordinary experiences, both negative and positive. The negative experiences during online learning are related to confusion, culture shock, dissatisfaction, stress, fatigue, and overwhelm, while the positive experiences are related to the ease of attending meetings simultaneously, carrying out activities at home and gaining new knowledge, especially in communication technology. Barriers and challenges experienced by teachers in online learning during the pandemic are technical and non-technical in nature.